If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 10 = 7x Reorder the terms: 10 + 6x = 7x Solving 10 + 6x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 10 + 6x + -7x = 7x + -7x Combine like terms: 6x + -7x = -1x 10 + -1x = 7x + -7x Combine like terms: 7x + -7x = 0 10 + -1x = 0 Add '-10' to each side of the equation. 10 + -10 + -1x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 0 + -10 -1x = 0 + -10 Combine like terms: 0 + -10 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| 4(4x-1)-(5x+1)=2(x+5)-33 | | 1/2d-3d=2 | | -11=1.8c+-80 | | -0.20-0.44a=0.13 | | 19x-30=179 | | p-0.2t=s | | 2x^3-2x^2y-24xy^2= | | 3-c-12=-5+c | | 17=-7+3p | | 8x+1+27x+4=180 | | y=2/3(72)+4 | | 4(j-2)=32 | | 2.8x+5-3.8x=9 | | 3x+1=15x-107 | | -22.89=1.7m | | 38x-102=164 | | y=2/3(15)+4 | | 3(4x+4)=16x+10-4x+2 | | 2x-1=-x-16 | | 9x+7=x+5 | | AQ=7x+8 | | 3.69/10=12*c | | 2f=3f+7 | | 22=9x+2-4x | | -3(1+8x)=-171 | | y=2/3(13)+4 | | 17x+80=90 | | Z/4+1=6-z/4 | | 9(t-7)-2(t-5)=10 | | -8b+2b=-7b+6 | | -16-(-t)=-23 | | 9x+7.38=3x+15 |